Exogenous cortisol causes a shift from deliberative to intuitive thinking. (February 2016) - Margittai, Zsofia; Nave, Gideon; Strombach, Tina; van Wingerden, Marijn; Schwabe, Lars; Kalenscher, Tobias
Highlights: Exogenous cortisol impairs cognitive reflection in men. Cortisol causes a shift from deliberative to intuitive thinking. Our findings provide one mechanism through which cortisol and acute stress impair decision making and cognitive performance. Abstract: People often rely on intuitive judgments at the expense of deliberate reasoning, but what determines the dominance of intuition over deliberation is not well understood. Here, we employed a psychopharmacological approach to unravel the role of two major endocrine stress mediators, cortisol and noradrenaline, in cognitive reasoning. Healthy participants received placebo, cortisol (hydrocortisone) and/or yohimbine, a drug that increases noradrenergic stimulation, before performing the cognitive reflection test (CRT). We found that cortisol impaired performance in the CRT by biasing responses toward intuitive, but incorrect answers. Elevated stimulation of the noradrenergic system, however, had no effect. We interpret our results in the context of the dual systems theory of judgment and decision making. We propose that cortisol causes a shift from deliberate, reflective cognition toward automatic, reflexive information processing.